PEMANFAATAN APLIKASI WHATSAPP GROUP SEBAGAI MEDIA PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Iim Halimatul Mu'minah; M. Kurnia Sugandi (Universitas Majalengka, 2021)
ABSTRACTThe Covid-19 pandemic forces the world community to define the meaning of life, the purpose of learning and the nature of humanity. The Government's sudden decision by dismissing or deciding that the learning process from school be carried out at home with online learning. With these problems, a solution or alternative is needed to answer these problems. Online learning is an alternative that can solve this problem. In the midst of the Covid-19 pandemic, it is recommended that learning process activities use innovative online learning media. Various media can be used to carry out online learning. Among them are virtual classes that use zoom meeting services, googlemeet, UMeetMe and others. However, these media require access to a strong internet network and large enough internet data so that it is too burdensome for students and parents. One of the online learning media that is easy, cheap, and instant to use is the WhatsApp Group application which can provide online classes through the Group chat feature. Through the WhatsApp Group application, a teacher can provide material briefly to students. The purpose of this study is to provide benefits and information regarding the use of the WhatsApp Group application as an online learning medium during the Covid-19 pandemic. The research method used is literature study or literature review. Keywords: WhatsApp Group Application, Online Learning Media, Covid-19 Pandemic.